Małe miasto jako przedmiot badań etnologicznych w Polsce. Stan i perspektywy - Odoj, Grzegorz (Studia Etnologiczne i Antropologiczne, 2011)
A small town is almost completely skipped in studies of Polish ethnologists. The main scientific output in this field constitute works by sociologists, demographers, geographers, historians and urbanists. The reason of ethnographers’ weaker interest in small town communities lies above all in the position of classical ethnography, functioning until recently, for which a traditional thread of research interest was the culture of farming village community. After all, a relatively small number, complex structure and sometimes complicated network of small social groups, people density, intensifying specific types of social interaction, concentration of different functions connected with urban organization and lifestyle are only some of premises reinforcing the attractiveness of small-town communities as a type of laboratory of ethnological studies and ethnological analyses. On the basis of an overview and short description of the research situation concerning the cultural issues of the small-town community as the research subject, one can see that there are many topics that are hardly examined or totally skipped in the studies. Still there are few works concentrating on the problems of attitudes, motivation of behaviours and interaction. The awareness aspects in the functioning of a small town as a collective community have been covered to a large extent. Thorough, regular and broader-scale studies on the phenomenon of cultural identity and local identification among the inhabitants of Polish small towns have not been conducted yet. After all the studies carried out with reference to a slightly big community, allowing for grasping all problems appearing in it, allow to explain the creation of social groups, their duration, development dynamics and coherence in a more precise and consistent way. It usually has a vital importance for formulating wider theoretical generalizations further on. A relative spacious isolation and closeness of social contacts enable the conditions to verify the already stated theses. What is more, a lot of interdependences existing within a small-town spacious-cultural system can constitute a basis for generalizations extrapolated on other levels and systems of a social life.